Efecto de distancia de siembra en el comportamiento agronómico del maíz (Zea mayz l.) hibrido 2b 604 en época de invierno en la zona de Quevedo. - Chila Cedeño, Johnny Geovanny (2015)
In order to evaluate the effect of plant spacing on the agronomic performance of hybrid maize (Zea mays L.) 2B 604 in winter time near Quevedo. Field research took a total of 16 plots and block design completely randomized with 4 treatments and 4 replications was used; was determined that there was no statistical significance for different populations The results indicate that the treatment showed the highest plant height was the treatment (T1) 0.50 X 0.30 m with an average of 2.18m, which showed the treatment insert taller cob was treatment (T1) 0.5 x 0.3 m, with 1.28 m, average diameter of ears, treatment (T3) showed the highest value with an average of 4,7cm the treatment showed the highest average ear length, was the treatment (T1) 0.5 x 0.3 m, with 15.89 cm, the mean weight of 100 seeds, treatment (T1) 0, 5 × 0.3 m showed the highest value 32,73g was determined that treatment T1 0.5 x 0.3 m with an average yield of 8898.6 kg ha -1 and this value statistically equal to treatment T2 0.6 x 0.3 m with an average of 8555.2 kg ha-1, which in turn are statistically higher than average of 0.7 T3 and T4 0.3 x 0.9 x 0.3 to 7215.9 kg ha-1 and 7094.7 kg ha-1 treatment that presents higher investment costs for Q1 production was 0.5 x 0.3 m at a cost of $ 1,415.00